THE INFLUENCE OF RELIGION ON THE COGNITIVE, EMOTIONAL AND BEHAVIORAL COMPONENTS OF A PERSON - Sargsyan , D. Yu.; Khachikyan , S. S. (Modern Psychology, 2025)
The article examines the influence of religion in the structural system of the individual, depending on the characteristics of religious faith, supernatural characteristics, sexual characteristics of the individual and crisis situations. Psychological interpretations of the mechanisms of influence used in religions are also presented. The purpose of the article is to analyze the role of religion in the cognitive, behavioral and emotional components of modern man from the point of view of psychological impact., one of these provisions is that value positions play a major role in the choice of behavior and determine the level of activity of personal activity, and the religious worldview in some cases rises above the level of personal identity and identification, it can become an indicator of national identity.
Keywords: personality; religion; religious faith; supernatural